2021
DOI: 10.3390/app11115127
|View full text |Cite
|
Sign up to set email alerts
|

Cationic and Anionic Dye Adsorption on a Natural Clayey Composite

Abstract: One of the main challenges for environmental sciences today is the effective treatment of dye-laden industrial effluents. This work aimed to study the potential of an untreated (natural occurring clayey composite) red clay (RC) for the adsorption of a cationic dye Basic Navy Blue 2RN (CNB) and anionic dye Drimaren Yellow CL-2R (ADY). We evaluated the effect of pH, dye concentration, and adsorbent concentration on the removal effectiveness to study the absorption process. Also, we studied the adsorption process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…It was also observed that there is an increase in the percentage of removal with the increase in the amount of mass of the adsorbent, since the adsorption of both dyes increases due to the increase in the area available for the exchange process between the solution and the surface until reaching the equilibrium. This type of behavior has been reported in other studies with different adsorbents [ 2 , 13 , 22 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. This analysis allows us to understand and know the limitations due to mass transfer, so this particularly important parameter must be considered [ 2 , 13 , 23 , 33 ].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…It was also observed that there is an increase in the percentage of removal with the increase in the amount of mass of the adsorbent, since the adsorption of both dyes increases due to the increase in the area available for the exchange process between the solution and the surface until reaching the equilibrium. This type of behavior has been reported in other studies with different adsorbents [ 2 , 13 , 22 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. This analysis allows us to understand and know the limitations due to mass transfer, so this particularly important parameter must be considered [ 2 , 13 , 23 , 33 ].…”
Section: Resultssupporting
confidence: 85%
“…After the adsorption of GV and PR with both bioadsorbents ( Figure 9 ) it was possible to notice that all the peaks disappeared exception of the signals at 14.7 and 21.9°, this effect is assigned to crystallinity increment of the materials increases [ 34 , 48 , 49 ]. The lattice parameters were also shown in Table 12 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations